Anthony & Cleopatra [Antónius a Kleopatra anglicky] - Shakespeare, William, 1564-1616; Shakespeare, William, 1564-1616.; Macaw Books (Leicester : Sweet Cherry Publishing, 2020)
"Anthony and Cleopatra" is a brilliant tragedy - drama of love and war by William Shakespeare. The play is set in ancient Rome and Egypt, and portrays actual events from Roman history. It revolves around its two main characters, Anthony, a Roman General, and Cleopatra, the Queen of Egypt. Anthony falls in love with Cleopatra, and throughout the play remains torn between his duty and his love for her.
A short narrative version of the play has been suitably adapted to help to introduce the play to young readers.
Keywords: Cleopatra, -- Queen of Egypt, -- -30 B.C. -- Pictorial works -- Juvenile fiction; Antonius, Marcus, -- 83 B.C.?-30 B.C. -- Pictorial works -- Juvenile fiction; Children's stories -- Pictorial works; čítam si sám (7+); cudzojazyčná literatúra